2015
DOI: 10.1165/rcmb.2014-0224oc
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Dysfunction and Lung Inflammation in the Female Mouse Model of Lymphangioleiomyomatosis

Abstract: Pulmonary lymphangioleiomyomatosis (LAM) is a rare lung disease caused by mutations of the tumor suppressor genes, tuberous sclerosis complex (TSC) 1 or TSC2. LAM affects women almost exclusively, and it is characterized by neoplastic growth of atypical smooth muscle-like TSC2-null LAM cells in the pulmonary interstitium, cystic destruction of lung parenchyma, and progressive decline in lung function. In this study, we hypothesized that TSC2-null lesions promote a proinflammatory environment, which contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…All animal procedures were performed according to a protocol approved by the University of Pennsylvania Animal Care and Use Committee. Briefly, 8-wk-old athymic nude female mice (NCRNU, Taconic) were injected with TMKOC cells (10 6 /100 l of PBS) into the tail vein, as previously described (4,13). Starting 3 days postinjection, mice received daily intraperitoneal injections of either diluent or 25 mg of axitinib (AG-013736; Tocris Bioscience, Bristol, UK; batch no.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All animal procedures were performed according to a protocol approved by the University of Pennsylvania Animal Care and Use Committee. Briefly, 8-wk-old athymic nude female mice (NCRNU, Taconic) were injected with TMKOC cells (10 6 /100 l of PBS) into the tail vein, as previously described (4,13). Starting 3 days postinjection, mice received daily intraperitoneal injections of either diluent or 25 mg of axitinib (AG-013736; Tocris Bioscience, Bristol, UK; batch no.…”
Section: Methodsmentioning
confidence: 99%
“…Cells isolated from bronchoalveolar lavage (BAL) were collected, counted (Beckman-Coulter, Miami, FL), and differentiated, and the remaining cells, not used for differential analysis, were frozen and further analyzed by quantitative RT-PCR (qRT-PCR), as previously described (4,14). Aliquots of the cell-free BAL fluid were stored at Ϫ80°C and further analyzed for cytokine levels by Multiplex (Aushon, Billerica, MA), and nitric oxide (NO) metabolites by chemical reduction and chemiluminescence using the Ionics/Sievers Nitric Oxide Analyzer 280 (NOA 280; Ionics Instruments, Boulder, CO), as previously described (3,4). Following lavage, lungs were fixed in formalin for hematoxylin and eosin staining and immunohistochemical (IHC) analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphangioleiomyomatosis (LAM) is a destructive cystic lung disease caused by LAM cells, which invade all the lung structures, including the lymphatics, airway wall, blood vessels, and interstitial spaces, therefore limiting the delivery of oxygen to the body. Moreover, LAM is a rare, progressive mesenchymal neoplasm mainly affecting childbearing age women [1][2][3][4]. The LAM cases are sometime difficult to diagnose because the disease symptoms are similar to other lung diseases (such as asthma, emphysema, and bronchitis).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that multimerized (high molecular weight (HMW)) and non‐multimerized (low molecular weight (LMW)) SP‐D are interconvertible structures . The HMW/LMW ratio is dependent on several factors such as posttranslational modifications of SP‐D by glycosylation and, in surrounding inflammatory conditions, by nitrosylation, oxidative damage and proteolytic degradation which result in degradation of SP‐D multimers and release of LMW breakdown products …”
Section: Introductionmentioning
confidence: 99%